[quotation] On revolutions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On revolutions: 'For the foreseeable future, the world will need to produce more food and other agricultural commodities from less land per capita. This will require higher yields per unit of land, water, energy and time. But it can be done, through...